Exploring Individual- and Court-Level Predictors of Mental Health Court Completion - Erwin, Jennifer Chadwick (2018)
Between 10 to 20% of jail inmates have a serious mental illness, while 4% of the general public has a serious mental illness. While incarcerated, inmates are required to have access to mental health care, however, access and quality of services provided is uncertain. During incarceration, adults with mental illnesses are more likely to be found in violation of rules and more likely to experience violence. Additionally, incarceration exacerbates symptoms of mental illness. A key nominal goal of incarceration is to reduce crime. Whether adults with mental illness experience prison in a way that reduces their likelihood of committing future crimes is questionable. Indeed, incarcerated adults with mental illness have especially high recidivism rates and experience more disciplinary issues than those without a mental health diagnosis.Mental health courts (MHCs) are the criminal justice systems response to addressing the revolving door of incarceration experienced by adults with mental illness. This dissertation addresses two questions about MHCs: First, are individual characteristics related to MHC completion?; and second, are court characteristics related to MHC completion rates? To address the first question, a review of court records found that participants with an index offense classified as a crime against another person were just as likely to graduate as those with more minor index offenses, like probation violations. To address the second question, a survey was sent to MHC coordinators nationwide to explore if and how elements of procedural justice influence MHC completion rates. An exploratory factor analysis resulted in a one-factor solution representing clarity. Ordinal logistic regressions revealed that clarity did not have a statistically significant relationship to either court completion or termination rates. Survey results are also discussed in further detail to provide a snapshot of how MHCs currently operate in the United States. The sample sizes for both studies were small, therefore replication is necessary. Additionally, a more accurate measure of procedural justice is needed because research has demonstrated that participants who perceive higher levels of procedural justice tend to have better court outcomes. Despite the limitations, these studies provide a first next step in MHC research